A systematic review of new imaging technologies for robotic prostatectomy: from molecular imaging to augmented reality - Rodler, Severin; Kidess, Marc Anwar; Westhofen, Thilo; Kowalewski, Karl-Friedrich; Belenchon, Ines Rivero; Taratkin, Mark; Puliatti, Stefano; Gómez Rivas, Juan; Veccia, Alessandro; Piazza, Pietro; Checcucci, Enrico; Stief, Christian Georg; et al. (Journal of Clinical Medicine, 2023)
New imaging technologies play a pivotal role in the current management of patients with prostate cancer. Robotic assisted radical prostatectomy (RARP) is a standard of care for localized disease and through the already imaging-based console subject of research towards combinations of imaging technologies and RARP as well as their impact on surgical outcomes. Therefore, we aimed to provide a comprehensive analysis of the currently available literature for new imaging technologies for RARP. On 24 January 2023, we performed a systematic review of the current literature on Pubmed, Scopus and Web of Science according to the PRISMA guidelines and Oxford levels of evidence. A total of 46 studies were identified of which 19 studies focus on imaging of the primary tumor, 12 studies on the intraoperative tumor detection of lymph nodes and 15 studies on the training of surgeons. While the feasibility of combined approaches using new imaging technologies including MRI, PSMA-PET CT or intraoperatively applied radioactive and fluorescent dyes has been demonstrated, the prospective confirmation of improvements in surgical outcomes is currently ongoing.